2019
DOI: 10.1302/0301-620x.101b8.bjj-2019-0173.r1
|View full text |Cite
|
Sign up to set email alerts
|

Pay for performance and hip fracture outcomes

Abstract: Aims Hip fractures are associated with high morbidity, mortality, and costs. One strategy for improving outcomes is to incentivize hospitals to provide better quality of care. We aimed to determine whether a pay-for-performance initiative affected hip fracture outcomes in England by using Scotland, which did not participate in the scheme, as a control. Materials and Methods We undertook an interrupted time series study with data from all patients aged more than 60 years with a hip fracture in England (2000 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(57 citation statements)
references
References 30 publications
3
53
0
Order By: Relevance
“…Furthermore, an absolute mortality risk of 14.9% was observed within 30 days in-hospital in Canadians admitted to hospital with any stroke in 2012 (25% aged 70–79, 38% aged ≥80) [ 30 ]. Considering that significant reductions in mortality risks associated with cardiovascular events have been reported over the past few decades [ 30 32 ], this data demonstrating a clear association between fragility fracture and mortality risk further highlights the need for effective measures to improve osteoporosis management and prevention of fragility fractures in older adults [ 11 13 , 17 19 , 21 23 ].…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, an absolute mortality risk of 14.9% was observed within 30 days in-hospital in Canadians admitted to hospital with any stroke in 2012 (25% aged 70–79, 38% aged ≥80) [ 30 ]. Considering that significant reductions in mortality risks associated with cardiovascular events have been reported over the past few decades [ 30 32 ], this data demonstrating a clear association between fragility fracture and mortality risk further highlights the need for effective measures to improve osteoporosis management and prevention of fragility fractures in older adults [ 11 13 , 17 19 , 21 23 ].…”
Section: Discussionmentioning
confidence: 97%
“…These criteria form the foundations of the best care evidence-based practice tariffs. These guidelines also offer healthcare providers financial incentives for delivering optimal care which is proven to improve neck of femur fracture outcomes [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are similarities and differences between the COPD audit programme and other UK national audits. The UK National Hip Fracture Database recently reported that pay-for-performance was associated with reduced mortality, shorter length of stay and fewer readmissions by comparing performance in England (where care quality was financially incentivised) to Scotland (where it was not) over a period of 10 years [ 31 ]. Other UK national databases such as the Myocardial Ischaemia National Audit Project (MINAP) have demonstrated optimal use of guidelines to be associated with better outcomes after myocardial infarction [ 32 ], suggesting potential gains in COPD can be large if adherence to guidelines could be improved.…”
Section: Discussionmentioning
confidence: 99%